Analysis of Teachers-Constructed Reading Comprehension Test - Meli Aulia Utami; Riska Rahman; Albiansyah Albiansyah (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
Constructing tests as part of assessments is the teacher's part in the teaching and learning process. Assessments have a role to evaluate student's comprehension and measure the extent of studying stages' success. Despite its significant value, teachers frequently construct tests without considering the main purpose of the test. This research concerns the way teachers construct their tests. To narrow the research scope, this research focuses on the reading comprehension test since reading comprehension is one of the main language skills for predicting learners' academic and professional development skills. The purpose of this study is to reveal the teacher stages in the construction of a reading comprehension test and the appropriateness of the test according to the test eligibility. To answer research questions, we adopt the qualitative research method. To collect data, we interview English language teachers from different schools who are teaching at different grades from Junior High Schools. Documentation is also be given since the teachers will need some of their final constructed test forms. To analyze the data, researchers calculate the number of HOTS and LOTS questions in the test, as the test eligibility standard. The study found that they are required to create their test indicators based on official general school/regulation indicators. It is also found that even though teachers are not obliged to provide dominant HOTS test items, HOTS test items are frequently discovered.